Wind-induced responses of tall buildings under combined aerodynamic control. (15th November 2018) - Zheng, Chaorong; Xie, Yu; Khan, Mahram; Wu, Yue; Liu, Jing
Highlights: A combined aerodynamic control, including shape optimization and air suction, is put forward. A simplified mass-spring model is introduced to calculate the wind-induced responses. Characteristics of wind-induced responses caused by combined aerodynamic control are analyzed. A quantitative discussion on the reduction of wind-induced responses is conducted. Abstract: The new trend towards constructing taller buildings makes modern tall buildings be increasingly susceptible to wind excitations. Therefore, a combined aerodynamic control, including the shape optimization of the cross-section (passive aerodynamic control) and air suction (active aerodynamic control), is put forward to achieve a more considerable reduction of the wind-induced responses of a tall building with square cross-section, so as to improve its wind-resistance performance. Firstly, based on the wind excitations acquired by wind tunnel test of four suction controlled tall building models with different cross-sections (consists of the square, corner-recessed square, corner-chamfered square and Y-shaped cross-sections, and are denoted as Models 1–4 respectively), the wind-induced responses of the prototype tall buildings and simplified mass-spring models are calculated using the time history analysis method. Secondly, effects of the suction flux coefficient C Q, shapes of the cross-sections and wind direction angles θ on the characteristics of the wind-induced responses are analyzed. The results show that the combined aerodynamic control is very effective in reducing the along-wind and across-wind responses at most cases, however, it can sometimes be unfavorable to the torsional responses. Among the four tall buildings, Model 2 has the best performance in the along-wind direction, with a maximum reduction of the extremum tip displacement of 34% caused by the shape optimization, and 29% caused by the air suction and a total of 63% caused by the combined aerodynamic control at a relatively low C Q ( C Q = 0.0159). However, the regularity is quite different for the across-wind responses; when θ is equal to 0°, the maximum reduction of the extremum tip displacement in the across-wind direction caused by the shape optimization and air suction are 49% for Model 4 and 47% for Model 1 respectively. Finally, a quantitative discussion on the reduction of the wind-induced responses of tall buildings caused by the combined aerodynamic control is conducted, which can provide a valuable reference for further studies or potential engineering applications.